Preparation and labeling of technitium-99m kit In pharmaceutical grade clean room (Journal of Chemical Engineering, 2014)
Technetium-99m radiopharmaceuticals are in widespread use owing to the availability and affordability of 99Mo/99m-Tc generators and the variety of kits for formulating the desired products. Together, they provide an array of specific tools for diagnosing a large number of diseases affecting the bones and major organs of the body such as the heart, brain, liver, kidney and thyroid. Nuclear medicine requires high quality radiopharmaceuticals and kits that are safe for administration and efficacious for a given application. In Bangladesh, no commercial production was done before this. This paper presents the theoretical basis of and describes the procedures for preparing three selected kits. Details of the ingredients are also included. The procedures described here can be used to develop manuals and standard operating procedures in Bangladesh. This report is expected to serve as a guide to radiopharmaceutical manufacturing centers and centralized pharmacies involved in the production of such kits in the current environment of Bangladesh. It will be a useful resource for many hospital radio pharmacy departments that routinely use the kits to compound 99m-Tc radiopharmaceuticals. Three kits namely: MDP, DMSA and DTPA were prepared. Paper Chromatography was involved to disparate the polar and non-polar part of the kit-solution and finally gamma spectrometry (HPGe) to deduce the Radiochemical Purity (RCP). By reviewing purity values, it was found that only DMSA has passed the 95% barrier which is the required percentage for safe application. This paper suggests that the findings require more practice and involve such exquisite points, which will contribute in the production of Tc-99m vivo-kits at Radioisotope Production Division (RIPD), AERE, INST and in their projected future mass production successfully. DOI: http://dx.doi.org/10.3329/jce.v27i2.17798 Journal of Chemical Engineering, IEB Vol. ChE. 27, No. 2, December 2012: 31-35